2019
DOI: 10.3892/etm.2019.8050
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of failing arterio‑venous dialysis graft by angioplasty, stent, and stent graft: Two‑years analysis of patency rates and cost‑effectiveness

Abstract: The objective of this prospective randomized single-center study was to compare primary and secondary patency rates, number of percutaneous transluminal angioplasty (PTA) interventions and cost-effectiveness among PTA, deployment of a stent, or a stent graft in the treatment of failing arteriovenous dialysis grafts (AVG) due to restenosis in the venous anastomosis or the outflow vein. Altogether 60 patients with failing AVG and restenosis in the venous anastomosis or the outflow vein were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The material and density of stents and the simulation conditions are identical, showing that varied biomechanical effects of stents are derived from different configurations. Among three venous stents commonly used in treating central vein or HD-circuit stenosis/occlusion, [26][27][28][29][30] similar radial force and flexibility are observed in SMART and Luminexx stents. Although the best performance in stress and strain on stent among the three, the equivalent stress and strain on vessels of SMART stent are the highest in expansion, and the strain is uneven.…”
Section: Discussionmentioning
confidence: 89%
“…The material and density of stents and the simulation conditions are identical, showing that varied biomechanical effects of stents are derived from different configurations. Among three venous stents commonly used in treating central vein or HD-circuit stenosis/occlusion, [26][27][28][29][30] similar radial force and flexibility are observed in SMART and Luminexx stents. Although the best performance in stress and strain on stent among the three, the equivalent stress and strain on vessels of SMART stent are the highest in expansion, and the strain is uneven.…”
Section: Discussionmentioning
confidence: 89%
“…In total, in all eight relevant studies (all RCTs), we included 867 patients for meta-analysis, who all had AVGs. [11][12][13][14][15][16][17][18] The patient populations of the two results were overlapping. 15 17 All studies were RCTs (four multicentre and two single-centre trials).…”
Section: Resultsmentioning
confidence: 99%
“…There was no mention of allocation concealment in two out of the seven prospective studies. 15 17 Blinding of participants and personnel was not possible, and we therefore allocated this as high risk of bias. We did not identify any detection or attrition bias in any prospective studies.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…This microinflammatory state is induced by the complementary system and endotoxins which activate the mononuclear macrophages, and triggers the release of many inflammatory factors. As the inflammatory response is aggravated, renal function continues to decline [17]. One study found [18] that patients who underwent maintenance hemodialysis had remarkably higher serum levels of TNF-α and IL-6 than normal controls.…”
Section: Discussionmentioning
confidence: 99%